ANALISIS PERBANDINGAN KINERJA KEUANGAN MENGGUNAKAN METODE FINANCIAL RATIO DAN ECONOMIC VALUE ADDED (EVA) PADA PT UNILEVER INDONESIA Tbk. TAHUN 2010 - 2013 - Syarifudin, Akhmad (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2015)
The company financial statements comprise the financial posts that help investors to assess which companies will be chosen. Many of the considerations made by the investor before investing in them is look at the financial performance of the company. Corporate performance assessment method is one important element in the company and important to know the company. This relates to whether the performance as long as it fits with who have desired the shareholders of the company.  The purpose of this research is to know the company's financial performance with using ratio analysis on financial aspects of the Return On Equity (ROE) and EVA as well as knowing how the comparison between the ratio analysis on financial aspects of the Return On Equity (ROE)  and application of the method of EVA as a measure of financial performance.  The type of research used in this research is descriptive using a quantitative approach. The object of the research was PT. Unilever Indonesia, Tbk and subsidiaries registered in BEI period 2010 - 2013. Results from the study explained that the results of the company's financial performance as measured by the overall financial ratio analysis on financial aspects of ROE  can be said to be very good, because for four years the value  ROE above industry average. While the results of the methods of EVA period 2010 – 2013 obtained a positive result (EVA > 0) and is increasing every year, which means that the company has succeeded in creating economic value added. In other words, during the period 2010 - 2013, the return expected by shareholders as owners of the company have been can be met by the company. Whereas the results of a comparison between the methods of ROE with EVA EVA method can be concluded that in the calculation of the company's performance is more accurate than the method of financial ratios, especially since ROE on the method parameters of EVA taken into account the existence of a cost of equity of the company. Keywords: EVA, Financial Performance, Financial Ratios